Vattimo’s Hermeneutical Nihilism - Šerpytytė, Rita (Problemos, 2004)
This article discusses the concept of Nihilism in the philosophy of Italian postmodern thinker G. Vattimo. The interpretation of nihilism is outlined in the context of a specific form of the thinking – the weak thinking – which is represented by Vattimo himself. The author shows that the structure of the weak thinking is based on the structure of a nihilistic movement. Vattimo’s concept of nihilism is distinguished in the relation of other concepts of nihilism. It becomes clear that Vattimo’s position derives from the sources of Heidegger’s and Nietzsche’s philosophy. The question that needs an answer is in which respect the weak thinking as a “theory” differs itself from other theories. The weak thinking reveals itself as a hermeneutic nihilism. The author draws the conclusion that namely the nihilistic type of the weak thinking distinguishes it among other anti-foundational forms of thinking (French postmodernism and especially Derrida deconstructional thinking).